1996
DOI: 10.1007/bf00182141
|View full text |Cite
|
Sign up to set email alerts
|

Electric shock-like sensations in 42 cancer patients: clinical characteristics and distinct etiologies

Abstract: We retrospectively evaluated 42 consecutive cancer patients manifesting electric shock-like sensations. Fourty three percent presented with Lhermitte's sign (LS), 24% with the previously described outstretching ir. abduction maneuver (OAM) of the arms, and 33% had both phenomena. Twenty nine patients had underlying polyneuropathy related to cisplatin-based chemotherapy in 27 and to thiamine deficiency in 2. Thirtreen patients had myelopathy which was induced by radiotherapy in 11. Patients with polyneuropathy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…First, LS is usually reversible. Only late onset LS may develop into CPRM [6,10,12,20,28,32]. Second, LS developed at maximum doses as low as 38.2 Gy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, LS is usually reversible. Only late onset LS may develop into CPRM [6,10,12,20,28,32]. Second, LS developed at maximum doses as low as 38.2 Gy.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic progressive radiation myelopathy (CPRM) can be preceded by delayed onset of Lhermitte sign (LS; 9-15 months after radiotherapy treatment) [6,10,12,20,28,32]. LS is a transient myelopathy with shock-like sensations from the neck to the extremities, typically after flexion of the neck, and can be evoked by different factors including radiotherapy [2,21,27,30].…”
mentioning
confidence: 99%
“…Damage to the dorsal root ganglia (DRG) may also produce ectopic impulse bursts ascending into the dorsal columns, potentially leading to Lhermitte’s phenomenon [4,31]. As DRG toxicity is a well-recognized feature of platinum-based chemotherapies [32], modulation of DRG excitability may contribute to the development of Lhermitte’s phenomenon in oxaliplatin-treated patients.…”
Section: Discussionmentioning
confidence: 99%
“…While Lhermitte’s phenomenon is typically associated with demyelinating lesions in the dorsal columns of the cervical spine [2], it has also been described with spinal compression, subacute combined degeneration of the spinal cord, Behçet’s disease and vitamin B 12 deficiency [3]. In the setting of malignant disease, Lhermitte’s phenomenon has been associated with radiation myelopathy, neoplastic spinal compression and chemotherapy-induced toxicity [4]. Regarding the latter, Lhermitte’s phenomenon has been reported in the context of worsening cisplatin-induced neuropathy [5] and with docetaxel treatment [6].…”
Section: Introductionmentioning
confidence: 99%
“…A retrospective analysis of 45 patients with known cisplatin-induced peripheral neuropathy demonstrated that 11 of these patients had LS [5]. Lossos et al [6] examined 42 cases of Lhermitte's in a cohort of oncology patients referred to a neuro-oncology clinic, and found 64% to be due to cisplatin. It has been suggested that LS is under-recognised and thus under-reported in oncology practice [1].…”
Section: Discussionmentioning
confidence: 99%